Respuesta :
[tex]\sf 2x^2 - 8x = - 7 \\ \\ Subtract \ -7 \ from \ both \ sides \ of \ the \ equation. \\ \\ 2x^2 - 8x - (-7 ) = - 7 - (-7) \\ \\ 2x^2 - 8x + 7 = 0 \\ \\ Use \ quadratic \ formula \ a = 2, b = -8, c = 7 \\ \\ x = \dfrac{- b \pm \sqrt{b^2- 4ac} }{2a} \\ \\ \\ x = \dfrac{-(-8) \pm \sqrt{(-8)^2 - 4 (2) (7) } }{2(2)} \\ \\ x = \dfrac{8 \pm \sqrt{8} }{4} \\ \\ x = 2 + \frac{1}{2}\sqrt{2} \ or \ x = 2 + \frac{-1}{2} \sqrt{2} [/tex]
Ur answer is the fourth one
Ur answer is the fourth one